Design of SCMA codebook based on chaotic signal and system performance analysis - Geng ZHAO; Yanyan MA; Yingjie MA (Tongxin xuebao)
Sparse code multiple access (SCMA) technology is one of the multiple access technology schemes for the new generation of 5G.In order to solve the transmission requirement of massive users,the logistic chaos sequence was proposed instead of the random sequence in the original system to select the codeword.The constellation method based on trellis coded modulation (TCM) subset segmentation with the mapping matrix was used to generate codebook in the encoder,and decoded through message passing algorithm (MPA) detection method.The simulation results show that the bit error rate (BER) is low when the system uses the pseudo-random sequence of chaos to select the codeword,and the system also performs well under the condition of high overload rate.